Ed tech's failure during the pandemic, and what comes after. (March 2021) - Reich, Justin
For decades, technology advocates have claimed that we are on the cusp of a complete transformation in education. But, as Justin Reich explains, such transformations have not yet come to pass. Even during the COVID-19 pandemic, teachers did not use technology to significantly alter their teaching. Instead, technology enabled them to maintain many of their classroom routines (using learning management systems or video conferencing) or supplement their usual instruction (using gamified apps). Teachers did, however, tinker with their methods throughout the pandemic, gradually improving over time. Reich suggests that this tinkering framework is a more realistic way to think about ed tech's potential to support teaching and learning .